ON THE LOCAL HYPERCENTER OF A GROUP - SILVA RAMOS,JOSÉ IVÁN (Universidad Católica del Norte, Departamento de Matemáticas, 2007)
We introduce a local hypercenter of an arbitrary group and study its basic properties. With this concept, it turns out that classical theorems of Baer, Malcev and McLain on locally nilpotent groups can be obtained as special cases of statements which are valid in any group. Furthermore, we investigate the connection between the local hypercenter of a group and the intersection of its maximal locally nilpotent subgroups.